Ultimate shear strength of perfobond shear connectors subjected to fully reversed cyclic loading. (1st December 2021) - Suzuki, Atsushi; Suzuki, Kaho; Kimura, Yoshihiro
Highlights: Results show perfobond shear connector behaviour under reversed cyclic stress. Finite element analysis results indicated stress transfer mechanisms. This comprehensive parametric study was conducted to ascertain influential factors. Analytical results suggest a new equation to evaluate ultimate shear strength. Outcomes reflect sophisticated composite effects of cyclically applied forces. Abstract: In general, a steel beam is assembled with a concrete slab using shear connectors. The application of perfobond shear connectors is increasing recently because of their high shear stiffness and strength. Nevertheless, the cyclic behaviour and performance of perfobond shear connectors subjected to fully reversed cyclic stress remain unclear. This research first constructs a finite element analysis model from reference to earlier experiment specimens. The element definitions and constitutive law of materials are calibrated based on available design guidelines and material test results. Furthermore, results of this research demonstrate a parametric study using the experimentally validated FEA model in terms of three resistance factors: 1) concrete dowel area, 2) cross-sectional area of penetrating reinforcement, and 3) concrete strength. Stress transfer mechanism investigations have deepened further, referring to FEA results. Moreover, analytical results clarify that earlier evaluation equations overestimate or underestimate the ultimate shear strength of perfobond shear connectors under cyclically applied stress. This study specifically examines the equivalent shear area of the novel evaluation equation, which has much higher accuracy than existing formulae. Ultimately, the ultimate shear strength under fully reversed cyclic stress has become predictable. The predicted behaviour is useful for the future application of perfobond shear connectors.